Relationships between online motivation, participation and achievement: More complex than you might think - Maggie Hartnett (Flexible Learning Association of New Zealand, 2012)
With the increasing importance and rapid growth of online courses, diversification of the student population, and the growing concern over retention rates, exploration of learner online participation and possible relationships with motivation and achievement behaviour is becoming increasingly relevant in higher education. Previous studies (Gerber, Grundt, & Grote, 2008; Picciano, 2002) have tended to explore links between learner activity and performance in online environments. But the relationships that may exist between motivation and participation (both in terms of quality and quantity of activity) in online contexts are not well understood. Indeed, participation, particularly active participation such as posting messages to online discussions, is frequently used as a proxy for motivation, with more active learners being perceived as more motivated. This paper presents findings of one aspect of a larger study (Hartnett, 2010) that explored the motivation of pre-service teachers situated within two separate and distinct online distance learning contexts. Self-report motivation data, achievement, and online usage statistical data, in conjunction with asynchronous discussion-forum transcripts, were used to explore possible relationships between motivation, participation, and achievement in these contexts. Analysis revealed important differences between and within the two cases (e.g., nature of the task and assessment approaches) that indicated situational factors played a key role in determining whether any significant relationships were present. In other words, various factors within the specific learning environment combined in complex ways to influence motivation to learn and the nature of student participation. In an age of increasing exploration and interpretation of online learner behaviour via automatically collected systems statistics (Beer, Jones, & Clark, 2009), these findings highlight the need to be cautious about using online activity as the only gauge for assessing student motivation in online contexts.